Understanding Heavy Drinking Practices and Alcohol-Related Harms: The Lived Experience of Nigerian Adolescents and Young Adults - Dumbili, Emeka W. (Journal of drug issues, 2024)
Many young people in Western countries are abstaining from alcohol consumption, but their Nigerian counterparts are adopting lifestyles that valorize alcohol use and heavy drinking rituals. This study explored heavy drinking practices and alcohol-related harms among young Nigerians (students and nonstudents) who use alcohol. Although participants were highly knowledgeable about the harms associated with heavy drinking, they reported heavy drinking and normalized intoxication. Most participants consumed between 3 and 12 bottles of beer, stout and other alcoholic beverages on a single occasion and suffered multiple incidents of intoxication and loss of control with adverse outcomes. Many participants suffered more than one health-related consequence, like vomiting, hangovers, and abdominal pain, while others fell sick, which incapacitated them for many days/weeks. Heavy drinking and intoxication also adversely impacted training and studies, as some participants could not go to work or attend lectures as planned. The findings highlighted the need for prevention and intervention strategies that seek to reduce heavy drinking and associated harms by targeting the social norms around heavy drinking specifically. Lessons learned in regions with youth drinking decline may inform public health strategies that can be implemented in Nigeria.